Formacao da base genetica e manejo dos recursos geneticos de mandioca: O caso do Brasil - Allem, A.C.; Goedert, C.O. (International Center for Tropical Agriculture, 1991)
The concept of genetic erosion is discussed, with particular reference to cassava in Brazil. National germplasm collections are listed with the corresponding no. of accessions; information is also provided on the plant breeding activities carried out. The potential of interspecific crossbreeding in cassava with wild Manihot species is discussed. In Brazil, wild Manihot species, particularly in the form of seed, are collected by the Centro Nacional de Recursos Geneticos (CENARGEN); both a small seed stock (15 species) and a small live collection (20 species) are maintained. The collection of woody wild species is considered prioritary. The interactions of CENARGEN with active germplasm collections in the country are indicated regarding collection, internal exchange, and germplasm introduction. A tentative organizational chart of a cassava germplasm collection is included. General indications are also provided on the handling of genetic resources. (CIAT)